Ситуационные негативы повседневности и адаптивные ресурсы человека - Ходоривская, Н. (Социология: теория, методы, маркетинг, 2004)
The article deals with the everyday negative situations often met by people and discusses them theoretically and in assessments by Ukrainian citizens. There are analyzed some disposition attributes of person in the context of actualization of social relations in adaptive situations.